The Effect of Interest In Al-Quran And Arabic Language Ability Towards The Achievement of Tahfizh Al-Qur'an - Gamal Abdel Nasier (Al-Hayat: Journal of Islamic Education, 2018)
The enthusiasm of Muslims in memorizing the Qur'an from time to time is increasingly felt. This can be observed in the emergence of boarding school programs that focus on the Qur'an or more precisely the Tahfidzul Al-Qur'an boarding school. Interest in memorizing the Qur'an and the ability to speak Arabic can be a person's influence in achieving the recitation of the Qur'an. The focus of this research will be to discuss the influence of the interest in memorizing the Qur'an and the ability of the Arabic language to memorize Al-Qur'an's achievements in the hope of contributing ideas for the future of Al-Qur'an education in Indonesia.Pesatnya animo dan semangat umat Islam dalam menghafal Al-Qur'an dari waktu ke waktu kian terasa. Hal ini dapat dicermati bermunculannya program pesantren-pesantren yang konsen tehadap Al-Qur'an atau lebih tepatnya pesantren Tahfidzul Al-Qur'an. Minat menghafal Al-Qur'an dan kemampuan berbahasa Arab kiranya dapat menjadi pengaruh seseorang dalam berprestasi terhadap hafalan Al-Qur'an. Fokus dalam penelitian ini akan membahas pengaruh minat menghafal Al-Qur'an dan kemampuan bahasa Arab terhadap prestasi hafalan Al-Qur'an dengan harapan dapat memberikan sumbangsih pemikiran untuk masa depan pendidikan Al-Qur'an di Indonesia.